2006
DOI: 10.1002/pmic.200500446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of substrates of the extracellular protease ADAMTS1 by DIGE proteomic analysis

Abstract: Proteolytic modification of components of the extracellular milieu by metalloproteinases plays important roles in the regulation of multiple cellular and physiological processes and pathological conditions. ADAMTS1 is a secreted enzyme of the ADAMTS (a disintegrin and metalloproteinase with thrombospondin motifs) family of proteases, which is related to angiogenesis and inflammation processes. Here, we describe a proteomic screening for putative ADAMTS1 substrates by analyzing the protein profiles obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 35 publications
3
51
0
2
Order By: Relevance
“…1,2 Mice with Adamts1-null mutation exhibit urogenital defects and female infertility because of impaired remodeling of ovarian extracellular matrix (ECM), but ovarian steroid production and lactation are normal. [3][4][5] A range of ECM proteins have been identified as potential ADAMTS1 substrates, including collagens, 6 nidogen, 7 and syndecan-4 8 ; however, the proteoglycans versican and aggrecan have been consistently shown to be key ADAMTS1 targets. 4,9,10 ADAMTS1 processing of versican is important in cell migration during wound healing, 11 endothelial cell invasion, 12 and remodeling of cardiac jelly ECM during heart morphogenesis.…”
mentioning
confidence: 99%
“…1,2 Mice with Adamts1-null mutation exhibit urogenital defects and female infertility because of impaired remodeling of ovarian extracellular matrix (ECM), but ovarian steroid production and lactation are normal. [3][4][5] A range of ECM proteins have been identified as potential ADAMTS1 substrates, including collagens, 6 nidogen, 7 and syndecan-4 8 ; however, the proteoglycans versican and aggrecan have been consistently shown to be key ADAMTS1 targets. 4,9,10 ADAMTS1 processing of versican is important in cell migration during wound healing, 11 endothelial cell invasion, 12 and remodeling of cardiac jelly ECM during heart morphogenesis.…”
mentioning
confidence: 99%
“…The arrows point to the proteins that exhibited significantly differential expression between RPM and control samples. A 1.5-fold cutoff (14) was chosen as a basis for investigating potential protein expression differences between data sets and to provide a basis for comparing the current data set with other studies. A total of 41 differentially expressed protein spots (4 down-regulated and 37 up-regulated) representing 20 unique proteins were successfully identified in the RPM samples compared to control samples (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The protein expression patterns of RSV lung tissue samples were compared with the controls. Protein spots with significant differences in abundance (more than 1.5-fold) (14) were selected for spot picking.…”
Section: Methodsmentioning
confidence: 99%
“…Using 2D-DIGE, Canals et al (2006) were able to identify Nidogen-1 and -2, two glycoproteins found in extracellular matrix, as potential substrates of ''a disintegrin and metalloproteinase with thrombospondin motif-1" protein (ADAMTS1) using 293T cell line expressing or not ADAMTS1. Using bronchoalveolar lavages of mouse model of allergic asthma and 2D-DIGE, Greenlee et al (2006) identified Ym1, S100A8 and S100A9 as MMP-2 and/or MMP-9 substrates.…”
Section: Two-dimension-differential Gel Electrophoresismentioning
confidence: 99%